The Life and Iconography of Gratian: a ‘mise au point’ part 2 - Murano, Giovanna (Saeculum Christianum, 2025)
In the first part of this study, I examined the limited biographical data available on Gratian (…–1145), the author of the canon law collection known as the Concordia discordantium canonum or Decretum. As we have seen, various sources agree that he was a monk, while some also state that he became Bishop of Chiusi in Tuscany at the end of his life. In this second part, I explore whether these biographical details found expression in iconography, which aspects of his life were emphasized in shaping his image, and the differing choices made by artists in Italy and north of the Alps - particularly in France – in their depictions of the Decretum’s author. W pierwszej części tego opracowania przeanalizowałam nieliczne dostępne informacje dotyczące biografii Gracjana (…–1145), autora zbioru prawa kanonicznego znanego jako Concordia discordantium canonum lub Dekret Gracjana. Jak widać, różne źródła są zgodne co do tego, że był on mnichem, a niektóre podają, że pod koniec życia pełnił funkcję biskupa Chiusi w Toskanii. Badania przeprowadzone w drugiej części wykażą, czy te dane biograficzne znalazły odzwierciedlenie w ikonografii, które informacje przeważyły nad innymi w kształtowaniu wizerunku Gracjana oraz jakie różne decyzje podejmowali artyści we Włoszech i poza Alpami, zwłaszcza we Francji, przedstawiając autora Dekretu.